2011
DOI: 10.1684/mrh.2011.0290
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium intake is associated with strength performance in elite basketball, handball and volleyball players

Abstract: Magnesium plays significant roles in promoting strength. Surveys of athletes reveal that intake of magnesium is often below recommended levels.We aimed to understand the impact of magnesium intake on strength in elite male basketball, handball, and volleyball players. Energy and nutrient intake were assessed from seven-day diet record. Strength tests included maximal isometric trunk flexion, extension, and rotation, handgrip, squat and countermovement Abalakov jump, and maximal isokinetic knee extension and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 12 publications
1
24
0
3
Order By: Relevance
“…In animals, a lack of dietary magnesium leads to increased free radical production [43], and magnesium supplementation eliminates free radical production induced by ischemia– reperfusion [44] and alcohol consumption [45]. Serum magnesium concentration and dietary magnesium intake are known correlates of muscle strength [46,47]. It has been recently shown that magnesium enhances glucose availability in the peripheral and central systems and increases lactates clearance in the muscle during exercise in rats [48].…”
Section: Discussionmentioning
confidence: 99%
“…In animals, a lack of dietary magnesium leads to increased free radical production [43], and magnesium supplementation eliminates free radical production induced by ischemia– reperfusion [44] and alcohol consumption [45]. Serum magnesium concentration and dietary magnesium intake are known correlates of muscle strength [46,47]. It has been recently shown that magnesium enhances glucose availability in the peripheral and central systems and increases lactates clearance in the muscle during exercise in rats [48].…”
Section: Discussionmentioning
confidence: 99%
“…Boron is known to attenuate exercise-induced rise in plasma lactate in animals [16] and to prevent magnesium loss in humans [17]. Serum magnesium concentration and dietary magnesium intake are known correlates of muscle strength [18,19]. Therefore, the minerals and trace elements in DOM may work cooperatively to sustain normal human performance.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium deficiency has been shown to impair physical performance, while several cross-sectional surveys have reported a positive association between magnesium intake or serum magnesium concentrations and outcomes related to muscle strength, muscle performance or muscle power [115]. For instance, one small cross-sectional study performed in 26 male athletes indicated a positive and significant association between magnesium intake and maximal isometric trunk flexion, rotation, hand grip, jumping performance, and isokinetic strength indicators [116]. Exercise has an impact on magnesium distribution and utilization (with magnesium being transported to locations where energy production is taking place, in response to exercise), and magnesium is necessary for muscle contraction and cardiorespiratory functions [115].…”
Section: Consequences Of Inadequate Status In Iron and Magnesium On Pmentioning
confidence: 99%